Using electronic medical record data to report laboratory adverse events. (1st February 2017) - Miller, Tamara P.; Li, Yimei; Getz, Kelly D.; Dudley, Jesse; Burrows, Evanette; Pennington, Jeffrey; Ibrahimova, Azada; Fisher, Brian T.; Bagatell, Rochelle; Seif, Alix E.; Grundmeier, Robert; Aplenc, Richard
Summary: Despite the importance of adverse event (AE) reporting, AEs are under‐reported on clinical trials. We hypothesized that electronic medical record (EMR) data can ascertain laboratory‐based AEs more accurately than those ascertained manually. EMR data on 12 AEs for patients enrolled on two Children's Oncology Group (COG) trials at one institution were extracted, processed and graded. When compared to gold standard chart data, COG AE report sensitivity and positive predictive values (PPV) were 0–21·1% and 20–100%, respectively. EMR sensitivity and PPV were >98·2% for all AEs. These results demonstrate that EMR‐based AE ascertainment and grading substantially improves laboratory AE reporting accuracy.